Arkeologi Alkitab dalam Fungsinya Sebagai Penjelasan dan Konfirmasi Alkitab - Lucas Partanda Koestoro (Balai Arkeologi Sumatera Utara, 2010)
AbstractThis article explores the relationship of information about an archaeology and biblical history. It will be conveyed how archaeological discoveries can explain and confirm that a sequence of events in the history of the Bible. The Bible, the holy book of Christian, is a history book and great truths of Christianity based on the facts disclosed. As an introduction, this paper is not an in depth study of a particular field but rather as an introduction to many areas.